Fibroblast Growth Factor 21 in Gestational Diabetes Mellitus and Type 2 Diabetes Mellitus - Katarzyna Gawlik; Tomasz Milewicz; Dorota Pawlica-Gosiewska; Iwona Trznadel-Morawska; Bogdan Solnica (Journal of Diabetes Research)
Objective. Women who develop GDM present a metabolic condition similar to that found in type 2 diabetes, characterized by impaired insulin response. Due to similar pathophysiologic mechanisms found between type 2DM and GDM, there is a great interest in finding markers that will lead to the understanding of a possible common origin to both diseases. The aim of this study was to determine serum FGF21 levels in 2DM and GDM and its correlation with selected metabolic parameters. Method. The study included 54 2DM patients and 52 nondiabetic individuals (control group 1) as well as 74 GDM women and 32 healthy pregnant controls (control group 2). Serum FGF21 was determined by enzyme-linked immunosorbent assay (ELISA), in all groups, and correlated with biochemical parameters of glucose metabolism and insulin resistance (HbA1c, HOMA index, TG, and HDL cholesterol). Results. FGF21 concentration was significantly higher in 2DM as compared with control group 1 (p<0.01). In the 2DM group, FGF21 was positively correlated with HOMA index (p=0.022, R=0.398). In the GDM group, the positive relationships with FGF21 were observed with glucose (p=0.020, R=0.264) and TG (p=0.013, R=0.283) while HDL-C levels were correlated negatively (p=0.004, R=−0.326). Conclusion. Serum FGF21 levels were significantly higher in 2DM patients than those without diabetes. Moreover, serum FGF21 levels were associated with selected metabolic parameters, suggesting that it may play acrolein glucose and lipid metabolism.